Підприємницькі стратегії щодо формування житлового фонду Донбасу у ХІХ – на початку ХХ століття - Закірова, С. (Краєзнавство, 2017)
У статті проаналізовано діяльність підприємців Донбасу щодо формування житлового фонду індустріальних підприємств. Зазначено урбанізаційні зміни краю внаслідок розвитку промисловості. На
підставі архівних документів доведено, що розвиток індустріального виробництва краю без створення
робітничих колоній був не можливим. Наявність житлового фонду на підприємстві виступала позитивною характеристикою на користь справи підприємця. Досліджено різні стратегії вирішення підприємцями проблеми житлового забезпечення працівників рудників та заводів регіону. Розглянуто рівень фінансування житлового фонду промисловцями та вартість користування житловими
приміщеннями робітниками. In the article the features of activity of businessmen of Donbass are considered to the sphere of housing
building as a result of capitalist development of industry, the terms of housing workers of mines and factories are
analyzed by the businessmen of region. On the basis of archival documents proved that the development of industrial
production of the region without the establishment of work colonies was impossible. Availability of housing
stock in the enterprise advocated positive characteristics in favor of the entrepreneur. It is investigated various
strategies to address employers the problem of housing for of workers of mines and plants in the region. It is defined
the level financing industrialists available housing and the cost to use the living quarters the workers.
At the enterprises of Donbass there were various the practice of providing housing workers: free, with partial
or full payment. In some large enterprises factory towns were divided into administrative and operational
colony. All the houses belong to the company, however, have a different accomplishment. The quality and size
of the housing stock was varied, varied and the conditions for its granting.
Entrepreneurs and the state recognized that hygienic living conditions of that period were not always satisfactory.
Difficult social situation of the settlements in the region has forced the state to establish special institutions
for the control of medical and sanitary-hygienic conditions of living of workers. В статье проанализирована деятельность предпринимателей Донбасса по формированию жилого
фонда индустриальных предприятий. Указаны урбанизационные изменения края в результате развития
промышленности. На основании архивных документов доказано, что развитие индустриального производства края без создания рабочих колоний был невозможным. Наличие жилого фонда на предприятии рассматривалось положительной характеристикой в пользу предпринимателя. Исследованы различные стратегии решения предпринимателями проблемы жилищного обеспечения работников
рудников и заводов региона. Рассмотрены уровень финансирования жилищного фонда промышленниками и стоимость пользования жилыми помещениями рабочими.